YOUTUBE CHANNEL OF DARS ARABI AS A MEDIA FOR THE SPREAD OF ARABIC LANGUAGE - Wida, Sabilla Setia; Ridho, Ghulam Muhammad; Mustofa, Syaiful (Universitas Islam Sumatera Utara (UISU), 2023)
The article aims to describe an analysis of the content on the YouTube as a medium for spreading Arabic language. The research uses descriptive qualitative research. The data sources used are primary data sources and secondary data sources. Primary data sources come from interviews while secondary data sources from books, journals and articles that support the research. The data analysis technique is in three stages, namely data presentation, data reduction, and drawing conclusion. The analysis is focused on the YouTube channel Dars Arabi. This channel presents educational Arabic learning content. The result of this study proves that there are several factors that support the spread of Arabic through the YouTube. The factors cover language structure-based content creation, utilizing You Tube as the most famous social media, focusing on disseminated educational program, and keeping developing content creation. Further, the content is created in a structured manner based on the curriculum of learning Arabic language. The creator of the content in the you tube always increases the content with selection. In conclusion, the YouTube channel of Dars Arabi succeeds to play the role of spreading Arabic language learning.